Revocable and traceable key-policy attribute-based encryption scheme - Fang QI; Yanmei LI; Zhe TANG (Tongxin xuebao)
The existing key-policy attribute-based encryption (KP-ABE) scheme can not balance the problem of attribute revocation and user identity tracking.Hence,a KP-ABE scheme which supported revocable and traceable was proposed.The scheme could revoke the user attributes without updating the system public key and user private key with a less update cost.Meanwhile,it could trace the user identity based on decryption key which could effectively prevent anonymous user key leakage problem.The proposed scheme was based on linear secret sharing scheme (LSSS),which was more efficient than tree-based access structure.Based on the deterministic q-BDHE hypothesis,the proposed scheme gave security proof until standard mode.Finally,compared with the existing KP-ABE scheme,the scheme has a shorter public key length,lower computational overhead and realizes the traceability function of user identity based on the revocable attribute,which has obvious advantages.